Comparison of Complication Risk for Open Carpal Tunnel Release: In-office versus Operating Room Settings. Issue 7 (12th July 2021) - Randall, Dustin J.; Peacock, Kate; Nickel, Katelin B.; Olsen, Margaret; Tyser, Andrew R.; Kazmers, Nikolas H.
Abstract : Background: Performing open carpal tunnel release (oCTR) in an office-based procedure room setting (PR) decreases surgical costs when compared with the operating room (OR). However, it is unclear if the risk of major medical, wound, and iatrogenic complications differ between settings. Our purpose was to compare the risk of major medical complications associated with oCTR between PR and OR settings. Methods: Utilizing the MarketScan Database, we identified adults undergoing isolated oCTR between 2006 and 2015 performed in PR and OR settings. ICD-9-CM and/or CPT codes were used to identify major medical complications, surgical site complications, and iatrogenic complications within 90 days of oCTR. Multivariable logistic regression was used to compare complication risk between groups. Results: Of the 2134 PR and 76, 216 OR cases, the risk of major medical complications was 0.89% (19/2134) and 1.20% (914/76, 216), respectively, with no difference observed in the multivariable analysis (adjusted odds ratio [OR] 0.84; 95% CI 0.53–1.33; P = 0.45). Risk of surgical site complications was 0.56% (12/2134) and 0.81% (616/76, 216) for the PR and OR, respectively, with no difference in the multivariable analysis (OR 0.68; 95% C.I. 0.38–1.22; P = 0.19). Iatrogenic complications were rarely observed (PR 1/2134 [0.05%], OR 71/76, 216 [0.09%]), which precluded multivariable modeling. Conclusion: These results support a similar safety profile for both the PR and OR surgical settings following oCTR with similar pooled major medical complications, pooled wound/surgical site complications, and iatrogenic complications.